Conversion of CO2 to Light Olefins Over Iron-Based Catalysts Supported on Niobium Oxide - da Silva, Igor A.; Mota, Claudio J. A. (Frontiers in Energy Research, 2019)
Four iron-based catalysts supported on niobium oxide (Nb2O5) were prepared by impregnation and characterized by TPR, FRX, DRX, and textural analysis. The catalysts were tested in a fixed bed continuous flow unit to convert a mixture of CO2 and H2 to hydrocarbons at atmospheric pressure. All catalysts were active in the range of 623–723 K. The selectivity to hydrocarbons and light olefins increases with the use of alkali metal promoters (K or Cs). At 673 K, the Fe-Cr-K/Nb2O5 showed 26% selectivity to light olefins, representing 5% yield with 20% CO2 conversion. The niobium oxide-supported catalysts were more active and selective than the same catalyst formulation supported on SiO2.